Building Character of Bugis Community in Bone From The Perspective of Quran and Local Wisdom - Muhammad Yusuf; Nahdhiyah Nahdhiyah; Kamaluddin Nurdin Marjuni (UIN Maulana Malik Ibrahim Malang, 2022)
This study is motivated by two things, namely Indonesia is the country with the largest Muslim population in the world, and the population of Indonesia has a high cultural diversity. This qualitative research applies a content analysis and semantic approach to analyze the texts and documents. Conceptually, proper education can shape character through the inculcation of religious values and local wisdom. At the same time, wise expressions in the Bugis advice are analyzed with a content analysis approach. The results of the analysis show two main points. First, character building starts from the human side. The Qur'an shows that character building must start from the inner dimension of the human being. It is indicated by the word 'anfus' in the Quran. Second, the central values of Bugis' local wisdom align with the universal values of the Quran, namely coaching that touches the inner dimension in the form of ideas, beliefs, and awareness of the importance of these noble values in attitudes and behavior. Penelitian ini dilatarbelakangi oleh dua hal yaitu Indonesia sebagai negara dengan penduduk muslim terbesar di dunia, dan penduduk Indonesia yang memiliki keragaman budaya yang tinggi. Penelitian kualitatif ini menggunakan pendekatan analisis isi dan semantik untuk menganalisis teks dan dokumen. Secara konseptual, pendidikan yang tepat dapat membentuk karakter melalui penanaman nilai-nilai agama dan kearifan lokal. Sementara itu, ungkapan bijak dalam petuah Bugis dianalisis dengan pendekatan analisis isi. Hasil analisis menunjukkan dua poin utama. Pertama, pembentukan karakter dimulai dari sisi kemanusiaan. Al-Qur'an menunjukkan bahwa pembentukan karakter harus dimulai dari dimensi batin manusia. Hal ini ditunjukkan dengan kata 'anfus' dalam Al-Qur'an. Kedua, nilai-nilai sentral kearifan lokal Bugis selaras dengan nilai-nilai universal al-Qur'an, yaitu pembinaan yang menyentuh dimensi batin berupa gagasan, keyakinan, dan kesadaran akan pentingnya nilai-nilai luhur tersebut dalam sikap dan perilaku.